KAJIAN PROPORSI SARI NANAS DAN KONSENTRASI STARTER TERHADAP AKTIVITAS ANTIBAKTERI KEFIR NANAS - Mayasari, Dewi; Nugerahani, Ira; Rahayu, Endang Sutriswati (Jurnal Teknologi Pangan dan Gizi, 2016)
This research uses Queen pineapple varieties juice because it have a high sugar content and contains antibacterial compounds such as phenol, chlorine, and iodine. The purpose of this study is to determine the effect of different proportions of pineapple juice and starter concentrations to the antibacterial activity of pineapple kefir. The experimental design that will be use is a Factorial Randomized Block Design (RBD) with two factors that are proportion of pineapple juice (N0= fruit juice; N1= 1:1, and N2= 1:2) and the concentration of starter (1% v/v and 10% v/v). Each treatment will be repeated 4 times. The main parameter that will be analyzed is the antibacterial activity against Staphylococcus aureus ATCC 25923 with diffusion wells method. The parameters that will be analyzed as a supporting data are pH, total acid, total yeast and BAL. Obtained data will be analyzed statistically by ANOVA (Analysis of Variance) at Î± = 5 % and continued with DMRT (Duncan's Multiple Range Test) to determine which level of treatment that gives significant differences. The proportion of pineapple juice had significant effect on the antibacterial activity of pineapple kefir, beside starter concentration had not significant effect on the antibacterial activity of pineapple kefir and the interactions between the two factors had not significant effect on the antibacterial activity of pineapple kefir with bacterial test Staphylococcus aureus ATCC 25923.